E-Stress Detector - Amrita, S; Joseph, Jobin; Shaji, Rona; Prasad, Athul; Gopal, Rahul (International Journal of Computer Sciences and Engineering, 2020)
Psychological wellness influence a noteworthy level of the world’s population every year. Stress is humans' response to various types of desires or threats. This response, when working properly, can help us to stay focused, energized and intellectually active, but if it is out of proportion, it can certainly be harmful leading to depression, anxiety, hypertension and a host of threatening disorders. The work has demonstrated the utility of online social information for contemplating despondency; be that as it may, there have been limited assessments of other mental well-being conditions. Cyberspace is a huge area for people to post anything and everything that they experience in their day-to-day lives. It can be used as a very effective tool in determining the stress levels of an individual based on the posts and updates shared by him/her. This is a proposal for a website which takes the username of the subject as an input, scans and analyses the subject's profile by performing sentiment analysis and gives out results. These results suggest the overall stress levels of the person and give an overview of his/her mental and emotional state.